2016
DOI: 10.1371/journal.pgen.1005863
|View full text |Cite
|
Sign up to set email alerts
|

UPF2-Dependent Nonsense-Mediated mRNA Decay Pathway Is Essential for Spermatogenesis by Selectively Eliminating Longer 3'UTR Transcripts

Abstract: During transcription, most eukaryotic genes generate multiple alternative cleavage and polyadenylation (APA) sites, leading to the production of transcript isoforms with variable lengths in the 3’ untranslated region (3’UTR). In contrast to somatic cells, male germ cells, especially pachytene spermatocytes and round spermatids, express a distinct reservoir of mRNAs with shorter 3’UTRs that are essential for spermatogenesis and male fertility. However, the mechanisms underlying the enrichment of shorter 3’UTR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
135
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(157 citation statements)
references
References 75 publications
(139 reference statements)
17
135
1
Order By: Relevance
“…In most known cases, NMD is downregulated as development proceeds [37, 4345], but notable exceptions are B-cell development and mesoderm differentiation, where NMD is upregulated [28, 38]. Male germ cell development is also likely to be accompanied by shifts in NMD magnitude, but it has not been resolved whether NMD is up- or down-regulated [26, 46, 47]. …”
Section: Introductionmentioning
confidence: 99%
“…In most known cases, NMD is downregulated as development proceeds [37, 4345], but notable exceptions are B-cell development and mesoderm differentiation, where NMD is upregulated [28, 38]. Male germ cell development is also likely to be accompanied by shifts in NMD magnitude, but it has not been resolved whether NMD is up- or down-regulated [26, 46, 47]. …”
Section: Introductionmentioning
confidence: 99%
“…Second, mRNA decay mechanisms are highly potent and responsible for the global elimination of RNAs during the transition from spermatocytes to spermatids, which contain ∼12 pg and ∼2.5 pg total RNA per cell, respectively 168 . Thus, long isoforms that contain destabilizing elements are rapidly degraded, probably by multiple decay mechanisms, including the degradation of mRNAs containing transposable elements, mediated by PIWI-interacting RNAs 129,169171 , and the nonsense-mediated decay pathway, which degrades transcripts with abnormally long 3′ UTRs (among others) 172,173 . Importantly, transcripts with short 3′ UTRs, which lack these destabilizing elements or features and thus escape mRNA degradation, are thought to be stored for translation at a later developmental stage, when transcription in globally inhibited.…”
Section: Figurementioning
confidence: 99%
“…Time-course analysis of the first wave of spermatogenesis confirmed that Upf1 and Upf2 are upregulated at the spermatocyte stage, with sustained or elevated expression in round spermatids. 4,14 However, there is also evidence that NMD is instead downregulated in spermatocytes (Fig. 3B, Model II).…”
Section: Nmd Regulation During Germ Cell Developmentmentioning
confidence: 94%
“…Evidence that NMD is upregulated as germ cell development proceeds comes from Bao et al, who found that many NMD genes, including Upf1 and Upf2, are upregulated in enriched spermatocytes and round spermatids compare with enriched immature germ cells (spermatogonia) 4 (Fig. 3A, Model I).…”
Section: Nmd Regulation During Germ Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation